Akodon cursor Winge, 1887 (Rodentia: Sigmodontinae): one or two species? New evidences based on molecular data - Nogueira, Cristina D. A.; Fagundes, Valéria (Zootaxa, 2008)
Akodon cursor Winge, 1887 (Rodentia, Muridae) occurs in dense rainforest in the Atlantic coast of Brazil, from northern (8 o S, Pernambuco and Paraíba) to southern (23-26 o S, São Paulo and Paraná) states. This species reveals high karyotype variability, ranging from 2n=16 to 14, and FN (number of autosomal arms) from 26 to 18. Previous cytogenetics studies suggested that each form (2n=14, 15 and 16) are distributed in a clinal pattern and represent polymorphisms in populations, with 2n=15 as an intermediate status (data from crossbreeding in laboratory). However, previous molecular analysis from literature revealed two reciprocal monophyletic clades, each of them composed by 2n=14-15 or 2n=16, suggesting the distinction of A. cursor (2n=14 and 15) from A. aff. cursor (2n=16). In this paper, we verified if the karyotype is the one-step characteristic to separate A. cursor and A. aff. cursor. We evaluated the divergence among northern and southern populations which accomplish 2n=14, 15 and 16 specimens in simpatry. Thus, we employed karyotype information and restriction fragment length polymorphisms analysis (PCR-RFLP) of mitochondrial gene cytochrome b in specimens with 2n=14, 15 and 16 from both northern and southern areas of occurrence. We observed two major clades (Φ ST >0.72), one including northern and the other southern populations, and all three karyotypes were clustered on both of them, revealing that the distinction of the populations are based on geographical level and not on karyotype structure. Previous contrasting molecular data were interpreted as a biased sample composition, since those samples included exclusively 2n=14 and 15 from southern and 2n=16 from northern populations. Thus, we proposed that 2n=14, 15 and 16 karyotypes belong to a single species, Akodon cursor.